ISLAMIC BANKING DEVELOPMENT AND FINANCIAL INCLUSION IN OIC MEMBER COUNTRIES: THE MODERATING ROLE OF INSTITUTIONS - Kamalu, Kabiru; Wan Ibrahim, Wan Hakimah Binti (Journal of Islamic Monetary Economics and Finance, 2021)
This study argues that the effect of Islamic banking development on financial inclusion is enhanced when there exist better quality institutions. A cross section dependency test, cointegration test, causality test, and system GMM (generalized method of moments) are applied to achieve this objective. Employing panel data from 30 Organisation of Islamic Cooperation (OIC) member countries over the period 2013-2018, the analysis suggests that Islamic banking promotes financial inclusion. Furthermore, it documents evidence which suggests negative and significant coefficients of the interaction between Islamic banking development and institutional quality. This means that Islamic banking development works well in promoting financial inclusion in countries with low institutional quality.